Targeting cognitive control to reduce anxiety in very young children: A proof of concept study. Issue 8 (16th June 2022) - Schroder, Hans S.; Ip, Ka I.; Hruschak, Jessica L.; Horbatch, Faith; Hall, Melissa; Liu, Yanni; Mannella, Kristin; Muzik, Maria; Rosenblum, Kate L.; Moser, Jason S.; Fitzgerald, Kate D.
Abstract: Objective: Underdeveloped cognitive control (CC)—the capacity to flexibly adjust to changing environments—may predispose some children to early onset anxiety disorders and represents a promising intervention target. The current study established and pilot‐tested "Camp Kidpower"—a novel group‐based, interactive CC training intervention—and assessed its impacts on behavioral and neurophysiological indices of CC among preschool children with elevated anxiety symptoms. Methods: Forty‐four anxious children (4–6 years) were enrolled in Camp Kidpower, delivered in four sessions over 10 days. Before and after camp, children's capacity for CC was measured using well‐validated, non‐trained behavioral tasks and error‐related negativity (ERN). Child anxiety symptoms were measured by parent report on the Spence Preschool Anxiety Scale. Results: Thirty‐two children completed the study, as defined by completion of pre‐ and follow‐up assessments and at least three camp sessions. From baseline to after camp, performance on behavioral tests of CC improved, ERN amplitude increased, and anxiety symptoms decreased. Conclusion: Results provide initial evidence that play‐based cognitive training targeted to behavioral and brain markers of CC reduces anxiety in preschoolers.